Electrospun tannin-rich nanofibrous solid-state membrane for wastewater environmental monitoring and remediation. (November 2022) - Hussain, Zahid; Ullah, Salim; Yan, Jincong; Wang, Zhili; Ullah, Ismat; Ahmad, Zia; Zhang, Ye; Cao, Yi; Wang, Li; Mansoorianfar, Mojtaba; Pei, Renjun
Abstract: Heavy metal, organic dyes, and bacterial contamination in water endanger human/animals' health, and therefore, the detection, adsorption, and capturing of contaminants are essential for environmental safety. Ligand-rich membranes are promising for sensors, adsorption, and bacterial decontamination. Herein, tannin (TA)-reinforced 3-aminopropyltriethoxysilane (APTES) crosslinked polycaprolactone (PCL) based nanofibrous membrane (PCL-TA-APTES) was fabricated via electrospinning. PCL-TA-APTES nanofibers possess superior thermal, mechanical, structural, chemical, and aqueous stability properties than the un-crosslinked membrane. It changed its color from yellowish to black in response to Fe 2+/3+ ions due to supramolecular iron-tannin network (FeTA) interaction. Such selective sensing has been noticed after adsorption-desorption cycles. Fe 3+ concentration, solution pH, contact time, and ligand concentration influence FeTA coordination. Under optimized conditions followed by image processing, the introduced membrane showed a colorimetric linear relationship against Fe 3+ ions (16.58 μM–650 μM) with a limit of detection of 5.47 μM. The PCL-FeTA-APTES membrane could restrain phenolic group oxidation and result in a partial water-insoluble network. The adsorption filtration results showed that the PCL-FeTA-APTES membrane can be reused and had a higher methylene blue adsorption (32.04 mg/g) than the PCL-TA-APTES membrane (14.96 mg/g). The high capture efficiency of nanocomposite against Fe 3+ -based S. aureus suspension than Fe 3+ -free suspension demonstrated that Fe 3+ -bounded bacterium adhered to the nanocomposite through Fe 3+ /TA-dependent biointerface interactions. Overall, high surface area, rich phenolic ligand, porous microstructure, and super-wetting properties expedite FeTA coordination in the nanocomposite, crucial for Fe 2+/3+ ions sensing, methylene blue adsorption-filtration, and capturing of Fe 3+ -bounded bacterium. These multifunctional properties could promise nanocomposite membrane practicability in wastewater and environmental protection. Graphical abstract: This study discussed the in-solution colorimetric detection of Fe ions, methylene blue adsorption-filtration, and the capturing of bacterial species using tannin-rich nanofibrous membrane via metal-phenolic network coordination. Image 1 Highlights: Tannin (TA)-reinforced APTES crosslinked fibers were fabricated via electrospinning. Fe ions bind to the crosslinked composite membrane due to FeTA complexation. FeTA membrane adsorbs up to 32.04 mg/g methylene blue dye and can be reused. Adsorption coupled filtration was more rapid than simple adsorption in removing dye. Tannin-rich membrane holds a high capture affinity against Fe 3+ bounded S. aureus.